COVERAGE OF THE SOCIAL ASPECTS OF THE ENTREPRENEURIAL FACTOR IN MODERN INTERNATIONAL THEORETICAL CONCEPTS - Zokirjonovich, Sobirjon (Journal of Fundamental Studies, 2023)
The article analyzes the coverage of the social aspects of the entrepreneurial factor in modern international theoretical concepts. In the article, the author focuses on the social views of Western and Russian sociologists, mainly the founder of the science of sociology O. From Conte’s point of view, the sociologist of today has appealed to the theories of scientists. For this reason, the article attempts to study the concepts of entrepreneurship in terms of periods, highlighting the sociological views of prominent sociologists on entrepreneurship and entrepreneurial activity. In addition, the article shows the factors influencing the formation and development of entrepreneurship, the role of well-known sociologists in society, their impact on stratification processes based on the views of scientists, and thus highlights their differences from other social groups.